Comparing the effect of cinnamaldehyde and metformin on expression of MiR320 and MiR26-b in insulin resistant 3T3L1 adipocytes - Yousof Naghiaee; Mahmood Vakili; Mohammad Mohammadi; Azra Mohiti; Javad Mohiti-Ardakani (Elsevier, 2021)
Background: Some micro-RNAs are linked with insulin resistance and their related signals. They can act as a predicting factor for respond to anti-diabetic medications. Cinnamon extract is considered as an herbal drug in Type 2 Diabetes. Purpose: This study was designed to evaluate the effect of Cinnamon extract on miR320 and miR26-b expression in insulin-resistant adipocytes in comparison to Metformin. Methods: 3T3L1 pre-adipocytes were cultured in DMEM medium and differentiated into adipocytes. Then, the cells were induced to insulin resistance with high glucose and high insulin medium, and treated with 100µg/ml Cinnamaldehyde, 10mM Metformin and combination of both. The expression of miRs was determined by quantitative real-time PCR method. GLUT4 protein expression was determined by western blotting method. Results: MiR320 was significantly over-expressed and conversely miR26-b expression was significantly decreased in insulin resistant 3T3L1 adipocytes compared to non-insulin resistant adipocytes (P-value<0.01). Cinnamaldehyde treatment, similar to Metformin decreased the content of miR320 and increased the content of miR26-b after 2h (P-value<0.01). Drug treatment increased GLUT4 protein expression (P-value<0.05). Conclusion: These findings suggest Cinnamaldehyde similar to Metformin can change miRs expression related to insulin resistance toward pre-insulin resistance conditions.